IGD Motifs, Which Are Required for Migration Stimulatory Activity of Fibronectin Type I Modules, Do Not Mediate Binding in Matrix Assembly - Maurer, Lisa M. (Public Library of Science, 2012)
Picomolar concentrations of proteins comprising only the N-terminal 70-kDa region (70K) of fibronectin (FN) stimulate cell migration into collagen gels. The Ile-Gly-Asp (IGD) motifs in four of the nine FN type 1 (FNI) modules in 70K are important for such migratory stimulating activity. The 70K region mediates binding of nanomolar concentrations of intact FN to cell-surface sites where FN is assembled. Using baculovirus, we expressed wildtype 70K and 70K with Ile-to-Ala mutations in (3)FNI and (5)FNI; (7)FNI and (9)FNI; or (3)FNI, (5)FNI, (7)FNI, and (9)FNI. Wildtype 70K and 70K with Ile-to-Ala mutations were equally active in binding to assembly sites of FN-null fibroblasts. This finding indicates that IGD motifs do not mediate the interaction between 70K and the cell-surface that is important for FN assembly. Further, FN fragment N-(3)FNIII, which does not stimulate migration, binds to assembly sites on FN-null fibroblast. The Ile-to-Ala mutations had effects on the structure of FNI modules as evidenced by decreases in abilities of 70K with Ile-to-Ala mutations to bind to monoclonal antibody 5C3, which recognizes an epitope in (9)FNI, or to bind to FUD, a polypeptide based on the F1 adhesin of Streptococcus pyogenes that interacts with 70K by the β-zipper mechanism. These results suggest that the picomolar interactions of 70K with cells that stimulate cell migration require different conformations of FNI modules than the nanomolar interactions required for assembly.